2017
DOI: 10.4467/16890027ap.17.004.6968
|View full text |Cite
|
Sign up to set email alerts
|

A Huge Diversity of Metopids (Ciliophora, Armophorea) in Soil from the Murray River Floodplain, Australia. II. Morphology and Morphogenesis of Lepidometopus platycephalus nov. gen., nov. spec.

Abstract: Abstract. The morphology and morphogenesis of a new Australian metopid ciliate, Lepidometopus platycephalus nov. gen., nov. spec., were studied using live observation, various silver impregnation methods, scanning electron microscopy, and morphometry. The new genus is outstanding in having epicortical scales (lepidosomes) and a strongly flattened and distinctly projecting preoral dome. Diagnostic features of L. platycephalus include a small, reniform body carrying an elongated caudal cilium, about 11 ciliary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…However, the cell division pattern of Castula specialis sp. nov. differs in some details from that in other metopids (Foissner & Agatha, 1999;Vďačný & Foissner, 2017: (1) all dome kineties are involved in the formation of the new adoral membranelles (vs. only some dome kineties in Lepidometopus platycephalus and M. boletus; although not explicitly stated, all dome kineties participate in this process in Metopus hasei and M. inversus). Here, the ratio between the number of dome kineties involved and the total number of dome kineties is assessed for the first time, as it might be of taxonomic significance.…”
Section: Morphogenesis Based On the Chinese Populationmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the cell division pattern of Castula specialis sp. nov. differs in some details from that in other metopids (Foissner & Agatha, 1999;Vďačný & Foissner, 2017: (1) all dome kineties are involved in the formation of the new adoral membranelles (vs. only some dome kineties in Lepidometopus platycephalus and M. boletus; although not explicitly stated, all dome kineties participate in this process in Metopus hasei and M. inversus). Here, the ratio between the number of dome kineties involved and the total number of dome kineties is assessed for the first time, as it might be of taxonomic significance.…”
Section: Morphogenesis Based On the Chinese Populationmentioning
confidence: 89%
“…General terminology mainly follows Lynn (2008), Foissner and Agatha (1999), Foissner (2016), Foissner (2017), andBourland et al (2020). In metopids, "setae" refer to the long cilia that can stiffen and are originated over the posterior one-quarter to one-third of the cell, different from caudal cilia that originate from the rear cell (Bourland et al, 2020).…”
Section: Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobic ciliates have received increased attention during the last decade. Most of the published studies deal with their taxonomy, diversity, and phylogenetic position using standard methods, for example, protargol impregnation, scanning electron microscopy, and single‐gene phylogenies (Bourland et al, 2014, 2017a, 2017b, 2020, 2022; Bourland, Rotterová, & Čepička, 2018; Bourland, Rotterová, Luo, & Čepička, 2018; Bourland & Wendell, 2014; Campello‐Nunes et al, 2020, 2022; da Silva‐Neto et al, 2016; Fernandes et al, 2018; Foissner, 2016a, 2016b; Li et al, 2017; Li, Zhuang, Pérez‐Uz, et al, 2021; Li, Zhuang, Wang, et al, 2021; Méndez‐Sánchez et al, 2022; Nitla et al, 2019; Orsi et al, 2012; Paiva et al, 2017; Poláková et al, 2021; Rotterová et al, 2018; Vďačný et al, 2019; Vďačný & Foissner, 2017a, 2017b, 2019; Zhuang et al, 2021, 2022). Other studies have provided insights into features of their anaerobic lifestyle, for example, evolution, metabolism, and symbioses with various prokaryotes (Beinart et al, 2018; Lewis et al, 2018; Muñoz‐Gómez et al, 2021; Newbold et al, 2015; Omar et al, 2017; Rotterová et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are close to 1000 species of ciliates that have been discovered and defined from terrestrial habitats (Foissner, 1993;Foissner et al, 2002), it has been estimated that this number would be much higher if the unexplored regions of the world were taken into consideration (Finlay and Fenchel, 1999;Foissner et al, 2002;Chao et al, 2006;Foissner et al, 2008). In recent years, molecular taxonomic studies have shown that many of the ciliate species that are morphologically indistinguishable, and the number of ciliates is far beyond what has been predicted (Vďačný and Foissner, 2017;Warren et al, 2017).…”
Section: Introductionmentioning
confidence: 99%